Higher Education in Taiwan Global, Political and Social Challenges and Future Trends - Hou, Angela Yung-Chi.; Chiang, Tung-liang.; Chan, Sheng-Ju.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This book discusses the situation of Taiwanese universities facing a rapidly changing domestic and global environment. It examines the social structure, drawing on professional perspectives, data-based and systematic analysis. The book fills gaps in the literature of higher education systems in East Asia, of which Taiwan is a representative nation. It provides the readers with great opportunities to understand the historical, political and cultural background of the higher education system in Taiwan and shares Taiwan$1 (Bs experience of how higher education institutions respond to the new challenges such as an ageing society, the pursuit of equity and inclusion, execution of talent recruitment, and the use of technological innovation. Finally the book discusses the implication of institutional research in university governance.s
Part I: Understanding Taiwan Higher Education in Historical, Political and Social contexts -- Chapter 1 Historical Development of Higher Education in Taiwan from Past to Present -- Chapter 2 Role and Functions of Taiwan Higher Education Providers -- Chapter 3 Neoliberalism and Public goods in Taiwan higher education -- Part II: Transforming Taiwan Higher Education into Global Players -- Chapter 4 Academic Competitions and Excellence Initiatives: Building World Class Universities -- Chapter 5 Quality Assurance and Quality Culture on Campus -- Chapter 6 Internationalization and Universities -- Chapter 7 Accountability and Academic Autonomy: Myths and Realities -- Chapter 8 Finance and University Governance -- Chapter 9 Curriculum and Entrepreneurialism -- Chapter 10 University Social Responsibility and Community Engagement -- Part III: Frontier of Rapid Changes -- Chapter 11 Doctor Education in Aging Society -- Chapter 12 Equity and Quality: Social mobility at Top Research Universities -- Chapter 13 A New Pathway for Taiwan Higher Education: Technological Innovation and MOOCS -- Chapter 14 A Gap between Student learning Outcomes and Employability -- Chapter 15 Talent Recruitment Policy: Professoriate and Brain Drain -- Chapter 16 Implication of Institutional Research in University Governance -- Chapter 17 Concluding Reflections: Prospects and Challenges for Taiwan Higher Education.
Keywords: Education, Higher; 9; Comparative education; Education and state; School management and organization; School administration; Higher Education; International and Comparative Education; Educational Policy and Politics; Organization and Leadership